The Evaluation of Accounting And Taxation Training - Sri Agustini; Muliyani Muliyani; Widiyanti Rahayu Budi Astuti; Wiwit Irawati (S1 Accounting Department, Faculty of Economic, Universitas Pamulang., 2021)
The Accounting and Taxation training that has been provided is expected to provide education to these students. Accounting and taxation are important subjects for them because some of these students attend SMK majoring in Accounting. The training includes an introduction to accounting such as making journals and other bookkeeping, as well as tax training including an introduction to the types of taxes and how to calculate taxes and report tax obligations. The purpose of this study was to describe the participants' satisfaction with (1) evaluation of the training on the level of satisfaction of participants (X1), (2) the level of graduation of the trainees (X2), (3) changes in the behaviour of participants after the training (X3). This research is quantitative descriptive research with a survey method. Measuring the level of satisfaction of participants using a 5-scale questionnaire with respondents totalling 67 participants in accounting and taxation training at the Nurul Ihsan Islamic Boarding School, Tangerang Selatan Banten. The analysis tool uses descriptive. The results of this study indicate that accounting and taxation training has an influence on the development of knowledge and value of accounting and tax reports for students who attend SMK majoring in Accounting.